A metal mesh net-packed method for improving thermochemical energy storage reactor performance by increasing the void fraction. (5th May 2023) - Ji, Wenjie; Zhang, Heng; Liu, Shuli; Li, Yongliang; Wang, Zhihao; Deng, Shihan
Highlights: A metal mesh net packed method is proposed to improve the thermochemical reactor. Cube aluminum mesh net with compact arrangement way has the better performance. The optimal void fraction of the thermochemical reactor is found about 0.5. The best energy density of 712.2 kJ/kg and thermal efficiency of 26.8% are achieved. Abstract: Thermal energy storage is important for solving the mismatch between energy supply and demand, for which thermochemical energy storage has proven effective. The accumulation of materials in the reactor leads to a large pressure drop and poor heat transfer, which is the main restrictor of enhanced performance. In this paper, a metal mesh net-packed method is proposed. Three net shapes – a pyramid, a cube and a cylinder – are adopted, each with two ways of arranging nets. Compared with the non-packed condition, the metal mesh net-packed method can increase the air temperature rise of 10.7 °C and lead to a pressure drop reduction of about 30%. In addition, it can increase energy storage density and thermal efficiency to their highest values of 712.2 kJ/kg and 26.8%, respectively, in the cube net-packed method with a compact arrangement. The higher inlet air velocity and relative humidity are better at augmenting performance. Furthermore, it has been proven that the optimal value of the void fraction is about 0.5 for superior system performance. The cube-shaped aluminium mesh net-packed method is the optimal method in this study, which provides references for further research.